Os demonstrativos contábeis publicados para a comprovação do atendimento do artigo 212 da constituição federal e a eficácia dos gastos com o desenvolvimento do ensino pelos municípios brasileiros. - Andrade, Márcio Sales de (2010)
The Brazil’s Federal Constitution determines that the cities and states apply not less than 25% of the somatory of the prescriptions taxes and constitutions transferences in the actions related to public education. To demonstrate the attendance of this constitution rule each being it must publish a constant countable demonstrative in the summarized report of the budgetary execution, instituted for the Secretary of the National Treasure – STN since 2000, after the validity of the Law of Fiscal Responsibility – LC 101/2000. It would carry it STN nº 560, of December 14th of 2001, instituted the manual of elaboration of the summarized report of the budgetary execution, hold of some countable pictures, where it has its Annex X the Demonstrative with Maintenance and Development of Instruction – MDE, to evidence the values destined to the education. Not despite the evidence of the application if of the one by means of a countable demonstrative, this doesn’t guarantee that the resources destined to the actions of education obey quality criteria. It doesn’t have in the demonstrative social indicating that allows to verifying the evolution in the level of education of the public networks, what it led to the institution of new pointers to evaluate the results of these public investments. The Index of Development of the Brazilian Education – IDEB, came to establish goals of social criteria by means of a punctuation that classifies the federative beings results partners in an accordance with presented, as the tax of approval and pertaining to school abandonment, for example. Ranking divulged in 2009 demonstrates the cities that had gotten the worst places had proven the attendance of article 212 of the Brazilian Federal Constitution, that is, doesn’t have a relation between the constitutional rule and the effectiveness of the administration of the education for the Brazilians cities; this is exactly the intention of this work.